Effects of sizes of additive particles on suspensions, microstructures, and electrical properties of ZnO varistors. Issue 5 (28th January 2020) - Yan, Ying; Ren, Xin; Cheng, Qi; Ruan, Xuejun; Wang, Manyu; Yu, Wenqi; Yao, Zheng
Abstract: The effects of the sizes of the additives on the dispersion of the mixed suspensions, the microstructures, and the comprehensive electrical properties of the ZnO varistors were investigated. The particle size distribution, the viscosity, and the zeta potential of the suspension were characterized to evaluate the effect of the sizes of the additives on the dispersion of the metal oxide particles. The potential gradient, the leakage current, the nonlinear coefficient, the voltage ratio, and the aging coefficient were considered to estimate the effect of the sizes of the additives on the performance of the ZnO varistors. The electrical testing results showed that a proper amount of milling of the additive particles could improve the comprehensive electrical properties, while an excessive milling produced the opposite effect. When the milling time of the additive particles reached 30 minutes, the dispersion of ZnO‐additive mixed suspension was the best. The as‐prepared varistors showed the optimal electrical performance with potential gradient of 310 V/mm, leakage current of 1 μA, nonlinear coefficient of 32.7, voltage ratio of 1.69, and aging coefficient of 0.59.